2015
DOI: 10.1097/pas.0000000000000344
|View full text |Cite
|
Sign up to set email alerts
|

Does Discontinuous Involvement of a Prostatic Needle Biopsy Core by Adenocarcinoma Correlate With a Large Tumor Focus at Radical Prostatectomy?

Abstract: When prostate needle biopsies are involved discontinuously by tumor, no consensus remains on the optimal method of tumor quantification. We investigated whether discontinuous biopsy involvement usually results from a large tumor focus or multiple small foci. Prostate needle biopsies with discontinuous tumor and corresponding whole-mounted radical prostatectomies from 2008 to 2013 were analyzed. Linear length and percentage of biopsy involvement were measured both including and subtracting the benign intervenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…They found that the presence of discontinuous tumor foci on biopsy was significantly more likely to correlate with actual bilateral disease. Meanwhile, Arias‐Stella et al demonstrated that discontinuous cancer foci in core biopsy represented a single tumor nodule in 31 (78%) of 40 radical prostatectomy specimens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the presence of discontinuous tumor foci on biopsy was significantly more likely to correlate with actual bilateral disease. Meanwhile, Arias‐Stella et al demonstrated that discontinuous cancer foci in core biopsy represented a single tumor nodule in 31 (78%) of 40 radical prostatectomy specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have attempted assessing the utility of different measurements of tumor extent in prostate biopsies where discontinuous cancer foci are present . Some of these studies have demonstrated that linear measurement in biopsy specimens better correlates with radical prostatectomy findings, such as the presence of extraprostatic extension and positive surgical margins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors recommend measuring the separate tumor foci end to end, and that includes the intervening benign glandular tissue in a core, instead of adding or ''collapsing'' the separate tumor foci ( Figure 10). [83][84][85][86][87] The end-to-end measurement has been shown by some studies to be more predictive of stage and risk for margin positivity at RP. The discontinuous tumor foci in the biopsy core are often the result of a single tumor from the corresponding region of the prostate.…”
Section: New Reporting Approaches and Recommendations Tumor Volume Inmentioning
confidence: 99%
“…In general, a common approach is to assume that discontinuous foci in a single biopsy represent a large, irregularly-shaped tumor. (27,28) However, some data support clonally different tumors. (26) Given that tumor volume percentage is a critical parameter used in the selection of prostate cancer management options such as active surveillance, enabling the assessment of clonal differences in the foci in cores with discontinuous foci may be important.…”
Section: Introductionmentioning
confidence: 99%